ECONOMICS OF CLIMATE CHANGE AT COP30: ALLERTS FROM A TRIBUTE TO WILLIAM NORDHAUS: Economics of Climate Change at COP30: Allerts from a Tribute to William Nordhaus - TOLEDO NETO, EDSON RODRIGO; MADEIRA NOGUEIRA, JORGE (RP3 - Revista de Pesquisa em Políticas Públicas, 2026)
Climate economics is now a recognized branch of economic theory that connects basic science with climate mitigation and adaptation policies, translating scientific predictions about physical systems into projections about economic growth and the well-being of societies. This article traces the evolution of this new climate approach from traditional economic worldviews, seeking to consistently address the following question: is there an economics of climate change? How a nascent economics of climate change is forging its path in developing responses to the climate crisis, pioneered by its patron William Dawbney. Nordhaus . Based on the theoretical framework that underpinned the work of William Dalbney Nordhaus , we sought to discuss the salient features of the models developed, as well as the controversies and debates of the last 60 years. In an environment of proliferating hypotheses and scenarios shrouded in uncertainty, Nordhaus can be recognized as a pioneer in the development of integrated economic assessment models (IAM) for climate policies, which underpinned trends and led to epic debates. From the 1970s to the 1990s, GHG taxation was the textbook of environmental economists, influenced by the Pigouvian Solution. Only in the 2000s did carbon markets become widespread as the primary remedy for the climate crisis, becoming dominant, despite the uncertainties surrounding these policies’ outcomes. Pricing the negative externalities of climate change, via price signals, also evolved through an evolutionary process.